A dialectic on validity: Explanation-focused and the many ways of being human - Bruno D. Zumbo (International Journal of Assessment Tools in Education)
In line with the journal volume’s theme, this essay considers lessons from the past and visions for the future of test validity. In the first part of the essay, a description of historical trends in test validity since the early 1900s leads to the natural question of whether the discipline has progressed in its definition and description of test validity. There is no single agreed-upon definition of test validity; however, there is a marked coalescing of explanation-centered views at the meta-level. The second part of the essay focuses on the author's development of an explanation-focused view of validity theory with aligned validation methods. The confluence of ideas that motivated and influenced the development of a coherent view of test validity as the explanation for the test score variation and validation is the process of developing and testing the explanation guided by abductive methods and inference to the best explanation. This description also includes a new re-interpretation of true scores in classical test theory afforded by the author’s measure-theoretic mental test theory development—for a particular test-taker, the variation in observed test-taker scores includes measurement error and variation attributable to the different ecological testing settings, which aligns with the explanation-focused view wherein item and test performance are the object of explanatory analyses. The final main section of the essay describes several methodological innovations in explanation-focused validity that are in response to the tensions and changes in assessment in the last 25 years.